Characterizing the Material Properties of Dutch Unreinforced Masonry. (2017) - Jafari, Samira; Rots, Jan. G.; Esposito, Rita; Messali, Francesco
Abstract: In the northern part of the Netherlands, the recent seismic activities have raised concerns about the behavior of unreinforced masonry structures which were not designed and constructed to resist seismic loading. The first step towards assessment of seismic behavior of masonry structures is to characterize the material properties. This characterization is the matter of importance, since the findings serve as input parameters for analytical and numerical models. To do so, destructive laboratory tests (standard and non-standard tests) have been carried out on samples extracted from existing masonry buildings. The compression, bending and shear properties of masonry were investigated in this research. The obtained properties were categorized with respect to masonry typologies and time periods.